2020
DOI: 10.3390/robotics9040106
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping Artificial Evolution to Design Robots for Autonomous Fabrication

Abstract: A long-term vision of evolutionary robotics is a technology enabling the evolution of entire autonomous robotic ecosystems that live and work for long periods in challenging and dynamic environments without the need for direct human oversight. Evolutionary robotics has been widely used due to its capability of creating unique robot designs in simulation. Recent work has shown that it is possible to autonomously construct evolved designs in the physical domain; however, this brings new challenges: the autonomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The system is based on a Robot Fabricator, the RoboFab, to implement robot (re)production without human assistance Hale et al (2019). The project is still running, but the experiences with an autonomous manufacture and assembly process revealed that real-world robot reproduction introduces new constraints on evolution that are not apparent in simulation Buchanan et al (2020).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is based on a Robot Fabricator, the RoboFab, to implement robot (re)production without human assistance Hale et al (2019). The project is still running, but the experiences with an autonomous manufacture and assembly process revealed that real-world robot reproduction introduces new constraints on evolution that are not apparent in simulation Buchanan et al (2020).…”
Section: State Of the Artmentioning
confidence: 99%
“…The solution to mitigate this issue is to use an unnatural trick: a sophisticated assessment of a new robot genotype (created by recombination and mutation of the genotypes of existing robots) before it is transformed into a new phenotype, that is, before starting the construction of the corresponding physical robot. A recent study introduced two notions to this end: manufacturability and viability Buchanan et al (2020). Manufacturability is the property that a certain body plan can indeed be constructed with the given system for robot (re) production.…”
Section: Genotype Filteringmentioning
confidence: 99%
“…Approaches that operate in a morphological search-space defined by pre-defined modules are particularly common [6,7,12,14] while increasingly the idea is being applied in soft-robotics, using voxel based simulators [7,8]. Recent work by Buchanan et al [1] extends the approach to a very complex morphological space that mixes some pre-defined modules (sensors, wheels, joints) with a 3d printed skeleton that can take any shape or form. Unlike the vast majority of previous work relating to joint body-control optimisation, the robots contain a variety of sensors, which introduces additional challenges regarding automate design of controllers: most previous approaches optimise controllers to produce actuation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we investigate the interaction between morphology evolution and controller learning in the rich morphological space defined in [1] that includes a variety of sensors and actuators using the hierarchical method shown in figure 1. We evaluate two forms of learning, used in conjunction with a single evolutionary approach to optimise morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation